Reproductive performance in cervical and postcervical artificial insemination (PCAI) with liquid boar semen in Gunghroo × Hampshire crossbreed pig in Nagaland - MAHAK SINGH; R TALIMOA MOLLIER; P H ROMEN SHARMA; J K CHAUDHARY (Indian Journal of Animal Sciences, 2020)
Genetic advancement for the modern swine industry is primarily accomplished through the use of reproductive biotechnology, mainly artificial insemination (AI). The objective of the present study was to compare the fertility outcome by cervical and post-cervical artificial insemination (PCAI) using normal (three billion) and reduced (one billion) number of spermatozoa in pig. Pluriparous weaned sows were grouped into 4 groups, i.e. Group- 1, AI with three billion spermatozoa by intra-cervical insemination; Group-2, AI with one and half billion spermatozoa by intra-cervical insemination; Group-3, AI with three billion spermatozoa by PCAI and Group-4, AI with one and half billion spermatozoa by PCAI. Non-significantly higher farrowing rate was recorded in Group-3 compared to Group-1. Post-cervical AI with lower number of spermatozoa (Group-4) resulted into farrowing rate which was similar to cervical insemination with higher number of spermatozoa (Group-1). There was significant difference in litter size at birth and litter size at weaning between Group-1 and 2. Litter size at birth and litter size at weaning was significantly higher in Group-4 compared to Group-2. Also, litter size at birth and litter size at weaning was significantly higher in PCAI animals (Group-2 and 4) compared to cervical inseminated animals (Group-1 and 2). In conclusion, PCAI with liquid boar semen was found to have improved farrowing rate, litter size at birth and litter size at weaning compared to cervical insemination.